Protective effect of luteolin on the transgenic Drosophila model of Parkinson's disease - Yasir Hasan Siddique; Smita Jyoti; Falaq Naz (Universidade de São Paulo, 2018)
In the present study we have studied the effect of 25, 50, 75 and 100 µM of luteolin on the transgenic Drosophila expressing human alpha synuclein. The doses of luteolin were established in diet and the PD flies were allowed to feed on it for 24 days. After 24 days of exposure the flies were assayed for climbing assay, oxidative stress markers, caspase-3 & 9 activity and dopamine content. The immunohistochemistry was also performed on the brain sections for the activity of tyrosine hydroxylase. The exposure of luteolin showed a dose dependent delay in the loss of climbing ability and activity, reduction in oxidative stress markers, caspase-3&9 activities and results in an increase in the dopamine content. The results obtained for the immunohistochemistry also supports the protective role of luteolin against the damage of the dopaminergic neurons.